Assesment of Osteoporosis in Medulla Spinalis Injured Patients - Zuhal Bayırlı Karakoyun; Belgin Erhan; Berrin Gündüz; Ayşenur Bardak; Gülsün Iska Elvan (Türk Osteoporoz Dergisi, 2011)
Aim: To investigate the relationship between osteoporosis and demographic features, clinical characteristics,risk factors in younger SCI patients. Materials and Methods: Between January-June 2009, all SCI patients admitted to our hospital evaluated and 58 patients who were younger than 50 years who had osteoporosis were enrolled.Patients age, gender, educational status, duration of injury, smoking, sunlight exposure and dietary habits were questioned. Neurological level, completeness, ambulation status and spasticity were assessed. Relationship between these findings with the severity of osteoporosis has been viewed. Results: There were 19 women. Mean age was 35,7 years. The mean time since injury were 117.7 months. 42 patients were paraplegia (17 complete), 16 were tetraplegia (4 complete).The most common osteoporotic site where the legs. There was no correlation between BMD values with age. In men, the legs and total body BMD were significantly lower.The effect of educational level on BMD was not found. No significant correlation was found between time since injury and BMD. In paraplegics, femoral neck and total femur Z-scores were significantly lower. In tetraplegics, Z scores of the arms were lower, but was not significant. Lumbar BMD values of complete patients were significantly lower than incompletes. Sunlight exposure and consumption of milk/milk products had not a significant positive effect on BMD. 8 patients had therapeutic ambulation, whereas 23 of them had community ambulation. Ambulation status of patients and the presence of spasticity was no effect on BMD. There was no significant correlation between BMD and the severity of spasticity. Smokers (n=19), bone density was lower in all regions except for femoral neck but were not significantly. Conclusion: Male gender, paraplegia, and incompleteness negatively effects the bone density. Age, time since injury, education level, spasticity, ambulation level, smoking, sunlight exposure and dietary habits has no significant effect on bone density. (Turkish Journal of Osteoporosis 2011;17:71-6)